Improving primary school children's motor skills: a physical education approach using circuit games with auditory sequencing - Aliriad, Hilmy; Da’i, Mohamad; Priadana, Benny Widya; Wigantara, Moch Rimba; Arifianto, Muchammad Ridwan (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Basic motor skills are an important foundation for physical activity and development in primary school children. However, many pupils have a delay in the development of these skills, so an innovative approach to motor learning is needed. One promising method is the integration of circuit play and auditory motor sequencing. Basic motor skills are an important foundation for physical activity and development in primary school children. However, many students struggle to develop these skills, necessitating an innovative approach to motor learning. One promising method is the integration of circuit play and auditory motor sequencing. Research Objectives: This study aims to investigate and test the effectiveness of integrating circuit games with auditory motor sequencing in improving basic motor skills in primary school children. Methods: In this research and development (RND) approach that involves several stages, namely game concept and design development, initial testing, and evaluation and revision based on test results. A total of 40 fourth-grade students from three elementary schools in Bojonegoro were selected through a purposive sampling technique. Data collection was done by analysing the basic motor skills of the students before and after the application of the method. Data analysis using the Content Validation Index (CVI) and Content Validity Ratio (CVR) to assess the validity of the contents of the model and T-test to measure the results of large-scale tests. Finding/Results: The study showed that integrating circuit games with auditory motor significantly improved the basic motor skills of primary school children. In addition, this method also increases students’ interest and active participation in physical activity. Conclusion: The integration of circuit games with auditory motors is effective in improving basic motor skills in primary school children. These findings support the importance of using innovative approaches to motor learning. This research contributes to the enrichment of motor learning models that can be adapted by physical education teachers. Recommendations for further research may include investigating auditory motor with other learning materials in the field of physical education.